Effects of Level of Retrieval Success on Recall-Related Frontal and Medial Temporal Lobe Activations - Daniela Montaldi; Andrew R. Mayes; Anna Barnes; Donald M. Hadley; Jim Patterson; David J. Wyper (Behavioural Neurology)
Brain dedicated single photon emission computed tomography (SPECT) was used to compare the neuroactivation produced by the cued recall of response words in a set of studied word pairs with that produced by the cued retrieval of words semantically related to unstudied stimulus words. Six of the 12 subjects scanned were extensively trained so as to have good memory of the studied pairs and the remaining six were minimally trained so as to have poor memory. When comparing episodic with semantic retrieval, the well-trained subjects showed significant left medial temporal lobe activation, which was also significantly greater than that shown by the poorly trained subjects, who failed to show significant medial temporal lobe activation. In contrast, the poorly trained subjects showed significant bilateral frontal lobe activation, which was significantly greater than that shown by the well-trained subjects who failed to show significant frontal lobe activation. The frontal activations occurred mainly in the dorsolateral region, but extended into the ventrolateral and, to a lesser extent, the frontal polar regions. It is argued that whereas the medial temporal lobe activation increased as the proportion of response words successfully recalled increased, the bilateral frontal lobe activation increased in proportion to retrieval effort, which was greater when learning had been less good.